A single lymphocyte culture for fragile X induction and prometaphase chromosome analysis. - Griffiths, M J (1991)
A single lymphocyte culture system is described which produces both reliable fragile X expression and elongated chromosomes for prometaphase analysis. This system, which is based on that described by Wheater and Roberts in 1987, involves the deoxycytidine release of a thymidine block. Eight fragile X positive subjects had an average expression level of 26%, with a range of 12% to 45%, using the thymidine/deoxycytidine protocol. This was comparable to the levels obtained in parallel cultures treated with thymidine alone or fluorodeoxyuridine.